Towards deeper understanding of a HiPIMS discharge by time-resolved optical plasma diagnostics - Britun, Nikolay; Palmucci, Maria; Konstantinidis, Stephanos; Snyders, Rony (International Conference on Plasma Surface Engineering, 2013)
Not available